The equation \( 134 - 3 = 14 \) is false.
Calculating the left side:
\( 134 - 3 = 131 \)
Since \( 131 \neq 14 \), the statement is false.
Therefore, the answer is 2.
11 answers
The equation \( 134 - 3 = 14 \) is false.
Calculating the left side:
\( 134 - 3 = 131 \)
Since \( 131 \neq 14 \), the statement is false.
Therefore, the answer is 2.
Apologies for any confusion. Let's evaluate it again:
The equation is \( 134 - 3 = 14 \).
If we calculate \( 134 - 3 \):
\[ 134 - 3 = 131 \]
Since \( 131 \neq 14 \), it means the equation is indeed false.
So the correct response is 2 (false). If you believe there was another aspect I misunderstood, please let me know!
Let's calculate each expression step by step.
Expression 1: \(-34 + 6 \cdot \sqrt{216}\)
Calculate \(\sqrt{216}\): \[ \sqrt{216} = \sqrt{36 \cdot 6} = 6\sqrt{6} \approx 14.7 \]
Now calculate \(6 \cdot \sqrt{216}\): \[ 6 \cdot 14.7 \approx 88.2 \]
Finally, calculate \(-34 + 88.2\): \[ -34 + 88.2 = 54.2 \]
So, Expression 1 evaluates to approximately \(54.2\).
Expression 2: \(4(2 + 6) \div 2 - 6\)
Calculate the expression inside the parentheses: \[ 2 + 6 = 8 \]
Now calculate \(4 \cdot 8\): \[ 4 \cdot 8 = 32 \]
Now divide by 2: \[ 32 \div 2 = 16 \]
Finally, calculate \(16 - 6\): \[ 16 - 6 = 10 \]
So, Expression 2 evaluates to \(10\).
Now we compare the two results:
We need to compare \(54.2\) and \(10\):
\[ 54.2 > 10 \]
Thus, the operator that should be inserted into the blank space is \(>\).
To determine if \( b = 3.5 \) makes the inequality \( 5b - 2 > 13 \) true, we can substitute \( 3.5 \) for \( b \) and check the inequality.
\[ 5(3.5) - 2 > 13 \]
\[ 5 \cdot 3.5 = 17.5 \]
\[ 17.5 - 2 > 13 \]
\[ 17.5 - 2 = 15.5 \]
\[ 15.5 > 13 \quad \text{(True)} \]
Since the inequality holds true, we conclude that the value \( 3.5 \) for \( b \) does make the inequality a true statement.
The answer is 1 (yes).
To find the value of \( x \) that makes the equation \( \sqrt{x} + 2 = 7 \) true, we can solve the equation step by step.
\[ \sqrt{x} = 7 - 2 \] \[ \sqrt{x} = 5 \]
\[ x = 5^2 \] \[ x = 25 \]
Now, let's check the options provided (20, 25, or 30):
For \( x = 20 \): \[ \sqrt{20} + 2 \neq 7 \]
For \( x = 25 \): \[ \sqrt{25} + 2 = 5 + 2 = 7 \quad \text{(True)} \]
For \( x = 30 \): \[ \sqrt{30} + 2 \neq 7 \]
So, the value of \( x \) that makes the equation true is \( \boxed{25} \).
To solve the equation \( \sqrt{2z - 2} = 5 \), we will isolate \( z \) step by step.
Square both sides of the equation to eliminate the square root: \[ 2z - 2 = 5^2 \] \[ 2z - 2 = 25 \]
Next, add 2 to both sides: \[ 2z = 25 + 2 \] \[ 2z = 27 \]
Now, divide both sides by 2: \[ z = \frac{27}{2} = 13.5 \]
Now we check the given options: 11.5, 12.5, or 13.5.
The value of \( z \) that makes the equation true is \( \boxed{13.5} \).